Karakterisasi Dan Aktivitas Fotokatalitik Green Synthesized Nanokomposit Fe3O4/TiO2 Menggunakan Ekstrak Daun Kelor Untuk Degradasi Methylene Blue - Br Situmorang, Dinda Agelia; Lubis, Ridwan Yusuf; Husnah, Miftahul (Rekayasa Material, Manufaktur dan Energi, 2025)
This research focuses on Fe3O4/TiO2 nanocomposites (produced through green synthesis) using moringa leaf extract to degrade methylene blue. The coprecipitation synthesis method was successfully employed to synthesize Fe3O4/TiO2. The aim of this study is to evaluate the effects of characterization results and photocatalytic activity on morphological structure, crystal size, and methylene blue degradation percentage. To assess these parameters, the study compared different mass composition ratios: 2:1, 1:1, and 1:2. The samples were characterized using Scanning Electron Microscopy (SEM), X-ray Diffraction (XRD), and UV-Vis Spectrophotometry.SEM results indicated that agglomeration occurred in the 1:2 mass ratio variation. XRD analysis showed that as the mass ratio increased, the crystal size decreased, with crystal sizes recorded at 30.71 nm, 28.38 nm, and 28.59 nm. UV-Vis results demonstrated that higher mass ratios corresponded to higher degradation percentages, reaching up to 97.80% for the FTMO1:2 sample.